CONNECTIVE TISSUE DISEASE-RELATED INTERSTITIAL LUNG DISEASE: COMPUTED TOMOGRAPHIC FEATURES (World Bulletin of Public Health, 2024)
Connective tissue diseases (CTD) include a spectrum of diseases affecting the connective tissue of the human body: they include autoimmune diseases characterized by chronic interstitial inflammation and fibrosis development. Pulmonary lesions may be misdiagnosed, since only in 20% of cases pulmonary changes precede bone and joint manifestations and in the early stages do not have a clear clinical picture. All pulmonary structures may be involved: pulmonary interstitium, airways, pleura, and respiratory muscles. Among these autoimmune diseases, rheumatoid arthritis (RA) is characterized by usual interstitial pneumonia (UIP), systemic lupus erythematosus (SLE) is characterized by the development of nonspecific interstitial pneumonia (NSIP) and lymphoacetabular interstitial pneumonia. Fibrotic NSIP may be an interstitial disease seen in patients with mixed connective tissue diseases (MCTD). This article shows CT findings to assist radiologists, pulmonologists, and rheumatologists in the diagnosis and management of this group of diseases.
Keywords: interstitial lung diseases; idiopathic interstitial pneumonia; common interstitial pneumonia